Circulating Exosomal SOCS2-AS1 Acts as a Novel Biomarker in Predicting the Diagnosis of Coronary Artery Disease. (9th April 2020) - Liang, Caihong; Zhang, Lulu; Lian, Xiaoqing; Zhu, Tiantian; Zhang, Yuqing; Gu, Ning
Abstract : Background and Aims . Critical roles of circulating exosomal long noncoding RNAs (lncRNAs) have been implicated in multiple diseases. However, little is known about their roles in coronary artery disease (CAD). The aim of the present study was to investigate the relationships between circulating exosomal lncRNAs and CAD and identify the aberrantly expressed disease-related lncRNAs as biomarkers in diagnosing CAD. Methods . The aberrantly expressed lncRNAs in plasma exosomes from CAD patients and controls were identified by microarray analysis and verified by quantitative real-time PCR (qRT-PCR). Then, the correlation between the expression level of candidate biomarker and clinic features in CAD patients, mild coronary artery stenosis (mCAS) patients, and controls was analyzed. Finally, we used the receiver operating characteristic (ROC) curve to examine the diagnosis value of candidate biomarkers. Results . The downregulated SOCS2-AS1 was determined by microarray analysis and verified by qRT-PCR in plasma from CAD patients in contrast to controls. The SOCS2-AS1 expression level in plasma exosomes was negatively correlated with PLT and Lpa. Moreover, CAD patients with elevated levels of plasma exosome-encapsulated SOCS2-AS1 were susceptible to multicoronary artery lesions. Additionally, the area under ROC (AUC) of SOCS2-AS1 was 0.704 (95% CI = 0.607–0.801, P < 0.001 ) for diagnosis of CAD. Conclusions . Plasma exosome-encapsulated SOCS2-AS1 was an independent protective factor against CAD and could be potentially used as a novel biomarker for the diagnosis of CAD.